The nucleation mechanism of succinic acid involved sulfuric acid - Dimethylamine in new particle formation. (15th October 2021) - Wang, Zhong-Quan; Liu, Yi-Rong; Wang, Chun-Yu; Jiang, Shuai; Feng, Ya-Juan; Huang, Teng; Huang, Wei
Abstract: Succinic acid (SUA) is a common dicarboxylic acid frequently observed in aerosols. Understanding the role of succinic acid in atmospheric new particle formation is essential to study the complicated nucleation mechanism. In this study, high-precision quantum chemical calculations and atmospheric clusters dynamic code (ACDC) simulations are used to investigate the nucleation mechanism of the (SA)x (SUA)y (DMA)z (0 = x, y, z ≤ 3) multicomponent system. The most stable molecular structures show that SUA can form relatively stable clusters with the SA-DMA system by hydrogen bond and proton-transfer interactions. Similar to SA molecules, SUA can provide protons to DMA when excess DMA molecules are available. ACDC simulations indicate that SUA can contribute to the cluster formation, especially at low sulfuric acid concentration and high succinic acid concentration. Moreover, the main cluster flux out of the SUA-containing system is along the non-diagonal (the number of acid molecules is greater than that of base molecules), which is different from the pure SA-DMA system. These clusters are stable enough to be present at a fairly high concentration, and could be a platform for growth into the larger sizes. This organic acid involved cluster formation may explain high nucleation rate at low sulfuric acid concentration and high organic acid concentration. Highlights: SUA may play an important role in particle formation and growth. The SUA molecule is similar to the SA molecule in providing protons to DMA. The nucleation mechanism may explain high nucleation rate at low sulfuric acid concentration.